Aboriginal Peoples Survey. 2017 [Canada] - Statistics Canada (Borealis, 2017)
The 2017 APS is a national survey of First Nations people living off reserve, Métis and Inuit aged 15 years and over. The 2017 APS represents the fifth cycle of the survey and focuses on transferable skills, practical training, use of information technology, Aboriginal language attainment, and participation in the Canadian economy. The 2017 APS collected unique and detailed data on employment, education, and health which are not available from any other source. For example, although the 2016 Census of Population collected data on certain aspects of labour market participation, the 2017 APS addresses additional topics such as job satisfaction, multiple employment, past job attachment, and willingness to move to improve career opportunities. The APS provides key statistics to inform policy and programming activities aimed at improving the well-being of Aboriginal Peoples. It is a valuable source of information for a variety of stakeholders, including Aboriginal organizations, communities, service providers, researchers, governments, and the general public. The survey is carried out by Statistics Canada with funding provided by three federal departments: Crown-Indigenous Relations and Northern Affairs Canada & Indigenous Services Canada (formerly Indigenous and Northern Affairs Canada), and Employment and Social Development Canada.